2014
DOI: 10.1590/s0104-12902014000200025
|View full text |Cite
|
Sign up to set email alerts
|

Doenças crônicas, problemas crônicos: encontros e desencontros com os serviços de saúde em itinerários terapêuticos de homens rurais

Abstract: ResumoApresenta-se uma análise do sistema de cuidado profissional a partir de itinerários terapêuticos de homens em situação de adoecimento crônico. Trata--se de uma pesquisa qualitativa, descritiva e exploratória realizada em uma comunidade rural, situada num município da metade Sul do Rio Grande do Sul. Para a geração de dados, empregaram-se entrevistas semiestruturadas, grupo focal, diários de campo e observação não participante, no decorrer dos meses de janeiro a julho de 2011. Como técnica de análise, uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
34

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(49 citation statements)
references
References 15 publications
0
15
0
34
Order By: Relevance
“…Moreover, the studies of the therapeutic itineraries make it possible to evaluate the HCN, considering the subjective dimensions, and not only performance indicators, that hardly account for the complexity of daily life and its repercussions on the health of the patients. 7 Faced with a lack of study on the subject, it is essential to know the therapeutic itinerary of people with TB in the care network, because it is essential that the health services offered guarantees universality, equity and integrality and care networks. Thus, the objective of this research was to describe the therapeutic itinerary of people with TB, in face of their health needs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the studies of the therapeutic itineraries make it possible to evaluate the HCN, considering the subjective dimensions, and not only performance indicators, that hardly account for the complexity of daily life and its repercussions on the health of the patients. 7 Faced with a lack of study on the subject, it is essential to know the therapeutic itinerary of people with TB in the care network, because it is essential that the health services offered guarantees universality, equity and integrality and care networks. Thus, the objective of this research was to describe the therapeutic itinerary of people with TB, in face of their health needs.…”
Section: Introductionmentioning
confidence: 99%
“…Although an expansion of health services has occurred in recent years, especially of what refers to basic care, poor distribution and human resource shortages still persist in rural and remote communities in the country. The movement of these professionals around these areas often does not allow the creation of a link, making them more concerned to offer a prompt response, focused on decisioncentered therapy of diseases with little exploitation of the life contexts of patients (21)(22) . For the rural women in the study, the medical reception manner revealed a rush in care, thereby compromising the quality of service, the resolution and the effectiveness of health actions.…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo que não haja muitos estudos que analisem o acesso aos serviços de saúde no rural (TOVAR-CUEVAS; ARRIVILLAGA-QUINTERO, 2014), verifica-se que ainda persistem vazios assistenciais e, também, grandes distâncias a serem percorridas pelas equipes e usuários na busca pela oferta e acesso aos serviços de saúde (OLIVEIRA et al, 2015;GALVÃO et al, 2015;UCHOA et al, 2011;PERETTO et al, 2011). No rural brasileiro, o modelo campanhista de atendimento em saúde ainda perdura; as equipes de saúde deslocam-se do urbano para o rural de acordo com agendas pré-estabelecidas e com periodicidade que pode variar de uma a duas vezes por mês, no formato de equipes móveis (BURILLE; GERHARDT, 2014). Em estudo na Metade Sul do Rio Grande do Sul, foi verificado que a lógica de atendimento de determinados agravos, como a violência, segue um "roteiro de atendimento" segundo o qual o adoecimento precisa ter hora ou momento certo para acometer esta população, ou seja, é preciso ter "sorte" em ser atendido (COSTA, 2012, p.195).…”
Section: Recompondo O Caminho Do Estudounclassified